Community College as a Gateway to Baccalaureate Success for International Students (Comparative & International Education Series, 2021)
Chapter 10|18 pages Community College as a Gateway to Baccalaureate Success for International StudentsBy Veronika Rozhenkova, Elizabeth S. ParkThe number of international students in the United States that transfer from community college to university continues to increase; yet, few studies have examined the college experiences of these students. Upon enrollment in a four-year institution, they become a part of the campus’s international student population and are frequently not being recognized as a potentially different subgroup of students with their own academic characteristics, challenges and needs. In this chapter, we aim to contribute to this knowledge by examining a case of a selective four-year public research university and comparing its international transfer students’ characteristics with those of traditional international students. Additionally, we identify potential ways of providing more adequate institutional support services for the targeted student population. We conclude with thoughts on extending this line of literature to better support transfer international students in their academic trajectory towards baccalaureate success.